Pubertal probiotic blocks LPS-induced anxiety and the associated neurochemical and microbial outcomes, in a sex dependent manner. (February 2020) - Murray, Emma; Smith, Kevin B.; Stoby, Karlene S.; Thomas, Bronwen J.; Swenson, Michael J.; Arber, Lauren A.; Frenette, Emilie; Ismail, Nafissa
Highlights: Pubertal LPS treatment causes enduring anxiety-like behaviour in males not females. Pubertal LPS treatment increases stress-induced brain activation in adult males. Pubertal probiotic blocks LPS-induced anxiety-like behaviour in males in adulthood. Pubertal probiotic blocks LPS-induced stress-induced brain activation in males. Abstract: Puberty is a critical period of neural development, and exposure to stress and inflammation during this period is thought to increase vulnerability to mental illness. The gut microbiome influences brain functioning and behavior and impacts mental health. Yet, the role of the gut microbiome during puberty, a period during which mental health conditions tend to onset, remains largely uninvestigated. We first examined age and sex differences in gut microbial changes among CD-1 mice exposed to an immune challenge (lipopolysaccharide; LPS) at 6 weeks of age (during the pubertal stress-sensitive period) or at 10 weeks of age (in adulthood) (Experiment 1). Compared to their adult counterparts, pubertal males and females showed more significant changes in gut microbial composition following LPS treatment, including the depletion of numerous bacterial genera such as Lactobacillus . Given the beneficial effects of Lactobacillus strains on stress and behaviour, we next investigated whether replenishment of the gut with the probiotic Lactobacillus reuteri ( L . reuteri ) throughout pubertal development would modulate LPS-induced sickness and enduring effects on memory dysfunction, anxiety-like behaviour and stress reactivity in adulthood (Experiment 2). LPS treatment at 6 weeks of age created enduring changes in anxiety-like behaviors among males only. Similarly, only males showed the protective effects of L . reuteri supplementation during puberty in preventing longstanding LPS-induced changes in anxiety-like behavior and stress-induced brain activation. These findings demonstrate that colonizing the gut with L . reuteri during puberty modulates sickness responses and enduring behavioural and neurochemical outcomes in a sex-specific manner. Therefore, colonizing the gut with beneficial microbes may protect against the development of mental illnesses in adulthood.